Hypogonadal men with psoriasis benefit from long‐term testosterone replacement therapy – a series of 15 case reports. (16th July 2015) - Saad, F.; Haider, A.; Gooren, L.
Summary: Psoriasis is increasingly recognised as a skin disease with far‐reaching systemic effects, associated with a high prevalence of comorbid disease such as cardiometabolic dysfunction, shifting the focus from a single organ disease confined to the skin to a systemic inflammatory condition. Chronic and systemic inflammation plays a major role in the development of these diseases, and there are striking similarities between the molecular and inflammatory pathways in psoriasis and atherosclerosis. In a single‐centre, cumulative, prospective registry study of 347 hypogonadal men (total testosterone ≤12.1 nmol l −1 ), fifteen men with psoriasis could be studied. Upon testosterone administration, the skin disease improved considerably. Scores on the Psoriasis Area and Severity Index and Physician Global Assessment for Psoriasis showed significant improvement for the first 24 months. Thereafter, these improvements were sustained. Upon testosterone treatment, C‐reactive protein declined significantly. There were significant improvements of obesity and of lipid profiles. Adipose tissue is now regarded as a source of inflammatory factors. These preliminary results deserve to be studied in a specifically designed study to investigate the effects of testosterone on psoriasis and its associated immunopathology.